Performing Presidential Age: "It's about how old your ideas are" - Barnes Lipscomb, Valerie (Age, Culture, Humanities: An Interdisciplinary Journal, 2024)
During a February surprise appearance on Late Night with Seth Meyers, President Joe Biden whipped out his trademark aviator sunglasses and traded quips with Meyers about a supposed conspiracy with Taylor Swift, much to the delight of the younger live audience. The next day, reviews were mixed about whether the president was trying too hard or did in fact manage to look hipper. To look younger. While US presidential nominees have been consciously performing their campaigns for decades, during this cycle, considering age as a performance has been especially prominent. Commentators and critics have specifically addressed the careful staging of persona that is central to presidential politics but is not always acknowledged as such.